Structured training on gross motor skills and physical fitness in 4–5-year-old children - Quan, Sheng; Liao, Yutong; Ji, Yulin; Zheng, Shuwen (Frontiers in Pediatrics, 2024)
Objective: Preschool children are in a period of rapid physical development, and improving their gross motor skills and physical fitness is quite important for their health. This study aimed to investigate the effectiveness of a structured physical training program in improving Chinese preschool children's gross motor development and physical fitness. Method: A sample of 80 children aged 4 to 5 from Fujian, China, were randomly assigned to the intervention group (N = 41), which received a 15-week structured physical training, while the control group (N = 39) continued with their daily physical activity. The Test of Gross Motor Development-3, and the National Physical Fitness Measurement Standards Manual -Preschool Children Version (2003) were assessed before and after the intervention.Results: A series of ANCOVA analyses revealed significant group differences in aspects of gross motor skills (F = 10.17, p ＜ 0.01) including locomotor skills (F = 5.31, p ＜ 0.05) and ball skills (F = 15.09, p ＜ 0.001) after controlling the effect of the age, sex, and pre-test scores. Moreover, the results also indicated a higher improvement in young children's physical fitness (F = 91.33, p ＜ 0.001) including their body shape (F = 5.05, p ＜ 0.05), health-related fitness (F = 43.09, p < 0.001), and skill-related fitness (F = 61.47, p < 0.001) in the intervention group over the control group. The results demonstrated that the effect size of the structured training on young children's health-related fitness (η 2 = 0.38) and skill-related fitness (η 2 = 0.50) was much stronger than on children's body shape (η 2 = 0.07).The structured training program effectively improved young children's gross motor skills and physical fitness.